توظيف تقنيات الذكاء الاصطناعي في الخدمات المرجعية بالمكتبات ومراكز المعلومات: دراسة تخطيطية لتصميم برمجيات المحادثة الآلية Chatbot - حسن، ياسمين أحمد عامر (المؤسسة العربية لإدارة المعرفة, 2022)
يأتي مجال الذكاء الاصطناعي وتعلم الآلة كوافد جديد يفرض نفسه بقوة على مختلف الأوساط الأكاديمية والمجتمعية، حيث تسعى العديد من التخصصات إلى تضمينه لتيسير أنشطتها ومهامها، ويعد مجال المكتبات وعلم المعلومات أحد التخصصات التي نهلت من هذا المجال في السعي نحو توظيف تقنيات الذكاء الاصطناعي المختلفة في أنشطتها ووظائفها الفنية والتطبيقية، وخاصة في الرد على استفسارات المستفيدين من المكتبات ومؤسسات المعلومات، وجاءت تقنيات إنشاء برامج المحادثة الآلية أو فيما عرف باسم Chatbot كأحد أبرز التقنيات التي وظفت في المكتبات. وتسعي هذه الدراسة الي تصميم برنامج محادثة آلية Chatbot قادر على تكشيف المعلومات واستخلاصها من الملفات، وذلك لاستخدامه في تقديم العديد من خدمات المعلومات، وخاصة في تقديم الخدمة المرجعية والرد على أسئلة واستفسارات المستفيدين، وتعتمد هذه الدراسة على المنهج الوصفي التحليلي، حيث تقوم هذه الدراسة برصد وتحليل أحد أبرز تطبيقات الذكاء الاصطناعي، وهي برامج المحادثة الآلية Chatbot وطريقة عملها، وكذلك تعتمد الدراسة على المنهج التجريبي في تصميم نموذج لبرنامج محادثة آلية Chatbot وتوظيفه في الخدمة المرجعية والرد على استفسارات المستفيدين وذلك بالاعتماد على لغة البرمجة Python بشكل أساسي في تصميم البرنامج، بالإضافة الي تضمين العديد من المكتبات الجاهزة المرتبطة بغلة البرمجة Python ومنها NLTK، Numpy، Wordnet، واختبار البرامج باستخدام طريقة Black Box Testing للتأكد من صحة النتائج المسترجعة.
The field of artificial intelligence and machine learning comes as a newcomer that imposes itself strongly on various academic and societal circles, as many disciplines seek to include it in order to facilitate their activities and tasks, and the field of libraries and information science is one of the disciplines that have benefited from this field in seeking to employ various artificial intelligence techniques in their activities. Its technical and applied functions, especially in responding to users’ inquiries from libraries and information institutions, and the techniques of creating automated chat programs or what is known as Chatbot came as one of the most prominent technologies employed in libraries. This study seeks to design a chatbot capable of indexing information and extracting it from files, for use in providing many information services, especially in providing the reference service and responding to users inquiries and analysis of one of the most prominent applications of artificial intelligence, which is chatbot programs and their method of work, as well as the study relies on the experimental approach in designing a model for a chatbot program and employing it in the reference service and responding to users inquiries by relying on the programming language Python mainly in program design. In addition to include many ready-made libraries related to the Python programming language, including NLTK, Numpy, Wordnet, and testing the program using the Black Box Testing method to ensure the correctness of the retrieved results.
Keywords: المكتبات -- مراكز المعلومات -- الخدمات المرجعية -- الذكاء الاصطناعي -- برامج المحادثة الآلية -- روبوت الدردشة